2013
DOI: 10.1111/1567-1364.12058
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the heteromeric coenzyme A-synthesizing protein complex (CoA-SPC) in the yeastSaccharomyces cerevisiae

Abstract: Coenzyme A (CoA) as an essential cofactor for acyl and acetyl transfer reactions is synthesized in five enzymatic steps from pantothenate, cysteine, and ATP. In the yeast Saccharomyces cerevisiae, products of five essential genes CAB1-CAB5 (coenzyme A biosynthesis) are required to catalyze CoA biosynthesis. In addition, nonessential genes SIS2 and VHS3 similar to CAB3 are also involved. Using epitope-tagged variants of Cab3 and Cab5, we show that both proteins cofractionate upon chromatographic separation, for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 20 publications
3
18
0
Order By: Relevance
“…Another protein, Nus1, has significant homology to Rer2 and Srt1, but does not have cis -IPTase activity (41). Both Srt1 (42) and Nus1 (22, 37, 43) have been localized previously to the LD. We found that Rer2 also localizes to the LD, as we detected Rer2-GFP in both membrane and LD fractions ( Fig.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Another protein, Nus1, has significant homology to Rer2 and Srt1, but does not have cis -IPTase activity (41). Both Srt1 (42) and Nus1 (22, 37, 43) have been localized previously to the LD. We found that Rer2 also localizes to the LD, as we detected Rer2-GFP in both membrane and LD fractions ( Fig.…”
Section: Resultsmentioning
confidence: 97%
“…The only de novo TG synthetic enzyme that we failed to detect in our LD proteome is Pah1, although it has previously been localized to the LD (36). Four of our six newly identified LD proteins increase the variety of lipid metabolic functions ascribable to the LD: Cab5 is involved in CoA synthesis (37), an important cofactor for many lipid synthesis reactions; Tsc10 catalyzes the second step in the synthesis of phytosphingosine, a long-chain base for sphingolipid production (38); Rer2 and Say1 function in dolichol and sterol metabolism, respectively, and are discussed below. Five proteins (Pet10, Yim1, YOR059C, and the newly identified YKL047W and YPR147C) do not have clear functions in yeast (see Table 1), but are likely to be involved in lipid metabolism as well.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This fused arrangement might also help to channel the CoaB product to the CoaC active site more effectively. The human CoaB and other eukaryotic orthologues form stable dimers due to the extra dimerisation region (Figure S5), but is also known in yeast that the entire CoA pathway assembles into a metabolon centred on CoaC 35,36 (known as CAB3). This hints that close proximity between the different active sites of the CoA enzymes is desirable and that substrate channelling of products and substrates between different enzymes might be important in this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…This is currently the subject of intensive research owing to the possibility of interactions with key signalling proteins, such as S6K (S6 kinase) and mTOR (mammalian target of rapamycin) [15]. A multifunctional CoA biosynthetic complex exists in yeast, with the Cab3 subunit of PPCD (phosphopanthenoylcysteine decarboxylase) acting as a scaffold for a CoA-synthesizing protein complex (CoA-SPC), which intersects with signalling pathways involved in salinity tolerance and cell cycle progression [16,17].…”
Section: Theme and Variations In Coa Biosynthesismentioning
confidence: 99%